Assessing the Leadership Competence of Master of Science in Mining Engineering Students. Issue 3 (1st September 2020) - Llamas Moya, Bernardo; Chamorro, Rosa M.; Reparaz, Carlos; Mora, Pedro
Abstract : The study evaluates the leadership capacity of students undertaking a master's degree in mining engineering at the Polytechnic University of Madrid. During the past four academic years, students undertook two self-perception questionnaires. The first used Dominance, Influence, Steadiness, Conscientiousness (DISC) methodology to classify students according to two parameters: rational–irrational and extrovert–introverted. The second assessed the ability of students to apply different leadership styles described in situational leadership theory. The attitude of the students showed a preference for rational aspects, with a low innovative attitude. Their preferred leadership style is participating and coaching, rather than managing or delegating. As a result, we propose a new learning method to improve crucial skills for the next engineers such as creativity, communication, teamwork, and leadership.